Business consulting para - Global Import Peru S.A. - Bazán Ribbeck, Fabiola Yolanda (2024)
Global Import Perú S.A.C., is a company that has been operating for two decades, since 2004 and it develops in the construction, real estate, and hardware sectors in Peru. Its field of action includes the import, sale, and wholesale and retail distribution of hardware items, lighting, electrical and electronic security equipment, plumbing equipment, among other products. The company, which began as a small retail hardware store, has grown and established itself as one of the few commercial representatives in Peru for international brands with high demand in the construction, real estate, and hardware sectors. This consulting report is aimed in that direction. Therefore, through the collection of information and analysis of all internal and external aspects of the company, opportunities, threats, weaknesses, and strengths were identified. Additionally, relevant data were obtained through interviews with Mr. Timber Huerta, managing director and founder of the company, who provided the necessary information to develop this document. The research revealed that the main problem of the company is the triple increase in sales operating expenses over a year, due to inefficient use of company resources. This situation creates complications in maintaining high profitability. The company would need to better integrate its processes and segment its business lines to better manage its operating expenses. Based on this diagnosis, two important solutions were proposed: ● The restructuring of the commercial team into specialized and segmented groups for each business line and client. ● The implementation of Enterprise Resource Planning (ERP) software that integrates commercial processes and customer management into a single platform. Both proposals were presented to Mr. Timber Huerta, managing director of Global Import Perú S.A.C., who approved the initiation of the ERP software implementation as the most urgent measure to address their main problem: the inefficient use of resources and loss of liquidity. The decision to implement the ERP as the primary measure to solve the problem is based on the idea that by tracking and defining the needs of each customer segment, better investment decisions can be made in the most profitable areas. Thus, with the approval of the company's management, the consulting team presented a minimal ERP implementation plan to be developed over a minimum period of 90 days. Estimating a result in the first year of implementation of 25% of the company’s sales with a net present value of NPV of 129,350.80 and the internal rate of return IRR of 96,8%.